Attribution of mental states and conversational awareness: a study with preschool students - Maluf, Maria Regina; Gallo-Penna, Eliana Cristina; Santos, Maria José dos (Paidéia (Ribeirão Preto), 2011)
The ability to attribute to oneself and to someone else mental states as desires, intentions and beliefs, has been called theory of mind. Recent studies show links between aspects of language and acquisition of theory of mind. This study investigates the relationship between conversational awareness, seen as an aspect of the pragmatic of language, and the attribution of mental states. Twenty eight children from 4 to 6 years old, both genders and low socioeconomic level participated in it. For the assessment of conversational awareness and theory of mind, tasks from the literature were used. The results showed the effects of age in favor of older children for the two variables and a positive correlation between them. These results are discussed based on other studies in the literature.